A business-cycle-model with monopolistically-competitive firms and Calvo wages: Lessons for Bulgaria (1999-2018) - Aleksandar Vasilev (Journal of Economics and Development, 2020)
Purpose: We augment an otherwise standard business cycle model with a rich government sector, and add monopolistic competition in the product market, and rigid prices, as well as rigid wages a la Calvo (1983) in the labor market.Purpose: We augment an otherwise standard business cycle model with a rich government sector, and add monopolistic competition in the product market, and rigid prices, as well as rigid wages a la Calvo (1983) in the labor market. Design/Methodology/Approach: This specification with the nominal wage rigidity,when calibrated to Bulgarian data after the introduction of the currency board (1999-2018), allows the framework to reproduce better observed variability and correlations among model variables, and those characterizing the labor market in particular. Findings: As nominal wage frictions are incorporated, the variables become more persistent, especially output, capital stock, investment and consumption, which helps the model match data better, as compared to a setup without rigidities. Originality/value: The computational experiments performed in this paper suggest that wage rigidities are a quantitatively important model ingredient, which should be taken into consideration when analysing the effects of different policies in Bulgaria, which is a novel result.
Keywords: E32; D43; D58; 330; business cycles; monopolistic competition; rigid (Calvo) prices; rigid (Calvo) wages